2013
DOI: 10.1210/jc.2012-3726
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Diagnosis of Primary Aldosteronism Using CYP11B2 Immunohistochemistry

Abstract: The present study clearly demonstrates that CYP11B2 immunostaining is a powerful tool for histopathological diagnosis of aldosterone overproduction in PA and for subtype classification of APA, multiple APCCs, unilateral multiple adrenocortical micronodules, and diffuse hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 25 publications
6
103
0
Order By: Relevance
“…More recently, generation of specific antibodies suitable for immunofluorescence has revealed that in APA a majority of cells express AS only, some cells express the 11b-and 17a-hydroxylases, but some cells are able to co-express the three enzymes . In 2013, two groups reported the use of specific antibodies against AS to improve the diagnosis of APA (Nanba et al 2013, Volpe et al 2013. However, similar to previous studies investigating CYP11B2 mRNA expression, in some APA AS is not detected.…”
Section: Familial Hyperaldosteronism Type IImentioning
confidence: 84%
See 1 more Smart Citation
“…More recently, generation of specific antibodies suitable for immunofluorescence has revealed that in APA a majority of cells express AS only, some cells express the 11b-and 17a-hydroxylases, but some cells are able to co-express the three enzymes . In 2013, two groups reported the use of specific antibodies against AS to improve the diagnosis of APA (Nanba et al 2013, Volpe et al 2013. However, similar to previous studies investigating CYP11B2 mRNA expression, in some APA AS is not detected.…”
Section: Familial Hyperaldosteronism Type IImentioning
confidence: 84%
“…However, similar to previous studies investigating CYP11B2 mRNA expression, in some APA AS is not detected. Semi-quantitative analysis revealed that AS expression was inversely correlated with tumor size and tumor volume, indicating that smaller tumors have higher AS expression per area and cell (Nanba et al 2013. These results may explain: i) why small APA below the detection limit of CT can result in clinical hyperaldosteronism and ii) why AS expression was not detectable in some large APA.…”
Section: Familial Hyperaldosteronism Type IImentioning
confidence: 95%
“…Mechanisms responsible for such aldosterone gradient in the adrenal vein in non-PA patients remain to be elucidated. Whether aldosterone-producing cell clusters with CYP11B2 expression 26,27 has a pathological significance in the higher side of adrenal in these 8 patients requires further investigation. The aldosterone gradient in the gray zone (LI=2-4) should be carefully interpreted in the subtype diagnosis of PA to avoid inappropriate adrenalectomy.…”
Section: Discussionmentioning
confidence: 99%
“…These clusters or nests of cells, therefore, differ from the typical zonation seen in human and rodent adrenals [zona glomerulosa (ZG), ZF, and zona reticularis (ZR)]. Interestingly, APCCs are also frequently found in adrenal tissue adjacent to APA, despite the low circulating renin/angiotensin levels found in patients with APA, suggesting that APCC production of aldosterone is renin-independent (autonomous) (15)(16)(17). Although these studies suggest a role for APCCs in autonomous aldosterone production and potentially, PA, previous reports have been limited to immunohistochemical analysis.…”
mentioning
confidence: 96%